carcinoma basocelular com invasão orbitária - Barros, Josenylda Calixto [UNESP]; Schellini, Silvana Artioli [UNESP]; Tagliarini, José Vicente [UNESP]; Sartorelli, Antonio Carlos [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (My University, 2007)
The purpose of this paper is to report a recidivate basal cell carcinoma of the eyelid with orbital invasion located in the inner canthus of the left eye. A 79 year old, male, Caucasian patient had a basal cell carcinoma removed from the left inner eyelid canthus 8 years ago and the edges of the resection were compromised by the lesion. The patient had recurrence of the lesion and orbital invasion. He was submitted to orbital exenteration and the ethmoid bone was removed too. The authors call attention to the necessity of correct diagnosis and followup to have success in the management of the patient.
Basal cell carcinoma with orbital invasion
Keywords: Carcinoma, basal cell/diagnosis; Case reports [publication type]; Eyelid neoplasms; Neoplasm invasiveness; Orbital neoplasms/secondary; Recurrence